Answer:
Answer letter D
Explanation:
-3x + 3y = 9
2x - 7y = -14
Let's start by simplifying both equations:
-3x + 3y = 9 (divide everything by 3)
2x - 7y = -14 (divide everything by 2)
We will then have:
-x + y = 3
x -
y = - 7
Then we sum both equations, eliminating x and isolating y to find its value!
y + (-
y) = 3 + (- 7)
y + (-
y) = - 4
Summing the fractions of y we have
-
y = - 4 .: y =
.: y = 1
(we found y!)
Now we substitute y in one of the previous equations to find x:
-3x + 3 × (
) = 9
-3x +
= 9
-3x = 9 -
![(24)/(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/thvyh2e5vho6pu4vqe0kql5i1cpyaioz3k.png)
-3x =
-
![(24)/(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/thvyh2e5vho6pu4vqe0kql5i1cpyaioz3k.png)
-3x =
![(21)/(5)](https://img.qammunity.org/2021/formulas/mathematics/high-school/zd00t3c8rih1d043nv08kdwk8fofctqha1.png)
x =
÷ -3 (this is tricky, but it's the same as
× -
)
x = -
.: x = - 1
(finally found x!)
Bringing everything together we have:
x = - 1
![(2)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/5jm6oitkd3lorjig5jfw17qliocw7lqrpz.png)
y = 1
![(3)/(5)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/pkh7trayrkeswyncl932pby2zkwu6svf5a.png)
I hope it helps :)